2019
DOI: 10.1002/csr.1746
|View full text |Cite
|
Sign up to set email alerts
|

Consumers' perception on corporate social responsibility: Evidence from Vietnam

Abstract: The purpose of this research focuses on examining the consumers' perception towards corporate social responsibility (CSR) in a developing country via the case of Vietnam. This study was conducted by face-to-face interview, and the questionnaire was mailed directly to consumers who are living in the urban and rural areas in Vietnam. The findings of this research are to clarify consumers' perception of CSR issues in Vietnam based on four dimensions of the CSR definition by Carroll in 1991. Therefore, the results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 57 publications
(67 reference statements)
2
57
0
1
Order By: Relevance
“…By identifying the underlying structure of multidimensional CSR measures (both performance and reputational) our findings also elaborate Huang, Do, and Kumar's () recent study of Vietnamese consumers. They found that consumer CSR priorities were dependent upon a country's level of economic development and consumer location.…”
Section: Discussionsupporting
confidence: 78%
“…By identifying the underlying structure of multidimensional CSR measures (both performance and reputational) our findings also elaborate Huang, Do, and Kumar's () recent study of Vietnamese consumers. They found that consumer CSR priorities were dependent upon a country's level of economic development and consumer location.…”
Section: Discussionsupporting
confidence: 78%
“…As a consequence, the concept of corporate social responsibility (CSR) appears. Although there is no consistency in the CSR concept (Huang, Do, & Kumar, 2019), CSR can be defined as the responsibility of enterprises for their impacts on society (The European Union Commission, 2011). In other words, to meet this responsibility, corporates need to involve their stakeholders to integrate economic, social, environmental, ethical human rights, and consumer concerns into their business operations and core strategy (Song & Jing, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Carroll's (1991) CSR pyramid proposes four basic components of CSR in American firms. This framework has been used to examine different aspects of CSR and includes the stakeholders' perceptions of CSR by Dusuki and Yusof (2008), Huang et al (2019), and Smirnova (2012). Carroll's (1991) CSR pyramid has also been applied to studies in CSR orientation (Ehie, 2016), impacts of CSR on a firm's performance (Lee et al, 2013;Long, 2015), and CSR practices (Baden, 2016).…”
Section: Theoretical Framework: Carroll's (1991) Csr Pyramidmentioning
confidence: 99%